2006
DOI: 10.1186/1471-2407-6-63
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trastuzumab and chemotherapy in advanced breast cancer after the failure of at least one earlier combination: An observational study

Abstract: Background: Combining trastuzumab and chemotherapy is standard in her2/neu overexpressing advanced breast cancer. It is not established however, whether trastuzumab treatment should continue after the failure of one earlier combination. In this trial, we report our experience with continued treatment beyond disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…[140][141][142] When used as a single treatment agent, trastuzumab increases the duration of survival, which is augmented by the administration of additional chemotherapeutic agents. 128,138,143 The most severe complication of trastuzumab therapy has been its potential to adversely affect cardiac function; however, the exact mechanism of its cardiotoxicity remains unclear.…”
Section: Targeted Biologic Therapies: Trastuzumab and Lapatinibmentioning
confidence: 99%
“…[140][141][142] When used as a single treatment agent, trastuzumab increases the duration of survival, which is augmented by the administration of additional chemotherapeutic agents. 128,138,143 The most severe complication of trastuzumab therapy has been its potential to adversely affect cardiac function; however, the exact mechanism of its cardiotoxicity remains unclear.…”
Section: Targeted Biologic Therapies: Trastuzumab and Lapatinibmentioning
confidence: 99%
“…Follow-up of patients who progressed on trastuzumab plus docetaxel in a phase II MBC trial reported a median postprogression survival time of 20 months for six patients who continued trastuzumab treatment beyond progression [52], and results from several retrospective analyses of case series also indicate that patients continue to derive benefit from trastuzumab after disease progression [53][54][55]. In a retrospective analysis of patients with HER-2-positive MBC, objective response rates and TTP were maintained in patients receiving two or more trastuzumab-based regimens (Table 2) [53].…”
Section: Trastuzumab Use Beyond Disease Progression In Mbcmentioning
confidence: 99%
“…In a retrospective analysis of patients with HER-2-positive MBC, objective response rates and TTP were maintained in patients receiving two or more trastuzumab-based regimens (Table 2) [53].…”
Section: Trastuzumab Use Beyond Disease Progression In Mbcmentioning
confidence: 99%
“…On the other hand, changing the traditional treatment paradigm in patients progressing on trastuzumab and administering further trastuzumab-based therapy beyond disease progression may have clinical benefit [65][66].This "treatment beyond progression" approach is increasingly being studied in clinical trials by combining trastuzumab either with chemotherapy [67][68] or with another targeted agent, such as the RTKI lapatinib [69]. Trastuzumab-DM1 (T-DM1) is an anti-HER-2 antibody drug conjugate comprising trastuzumab linked to the maytansine derivative DM1.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%